Supraclinoid direct carotid-cavernous sinus fistula - Che Ani, Mohd Firdaus; Kumar, Ramesh; Md Noh, Mohamad Syafeeq Faeez; Muda, Ahmad Sobri (British Institute of Radiology, 2018)
Carotid-cavernous fistulas (CCFs) are vascular shunts between the carotid arterial system with direct drainage into the cerebral venous system, mainly to the cavernous sinus. Direct CCF is a well-recognised complication following head trauma. Classically in direct or traumatic CCF, vessel wall tear occurs at the cavernous segment of the internal carotid artery, between the fixed and free segment. Tears at the supraclinoid segment are rare. We report a case of an internal carotid artery supraclinoid segment pseudoaneurysm, with a direct communication with the cavernous sinus, draining into the superior ophthalmic vein.